PENGARUH EFIKASI DIRI DAN PERSEPSI KESEJAHTERAAN GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI - Aida Hannani; Jaryanto Jaryanto (Universitas Sebelas Maret, 2025)
Abstract This research aims to examine the effect of self-efficacy and perception of teacher welfare on the interest in becoming a teacher among students in the Accounting Education study program. This research is a quantitative causality study. The population in this research were active students of the Accounting Education study program, class of 2021-2024. The sampling technique used in this study was proportionate stratified random sampling. The sample used in the research consisted of 176 students. Data collection techniques used questionnaires. The research instrument test used validity and reliability tests. The analysis prerequisite test used the classical assumption test, while the hypothesis test used multiple regression analysis, t-test, F-test, and coefficient of determination assisted by the SPSS version 26 program. Based on the results of the research, it can be concluded: 1) There is a significant influence between self-efficacy and interest in becoming a teacher with a significance value in the t-test of 0.000 (Sig. <0.05); 2) There is a significant influence between perceptions of teacher well-being and interest in becoming a teacher with a significance value in the t-test of 0.002 (Sig. <0.05); 3) There is a significant influence between self-efficacy and perception of teacher well-being on interest in becoming a teacher with a significance value in the F test of 0.000 (Sig. < 0.05).Keywords: interest in becoming a teacher, perception of teacher welfare, self-efficacy Abstrak Penelitian ini bertujuan untuk menguji pengaruh efikasi diri dan persepsi kesejahteraan guru terhadap minat menjadi guru mahasiswa program studi Pendidikan Akuntansi. Penelitian ini termasuk penelitian kuantitatif kausalitas. Populasi dalam penelitian ini adalah mahasiswa aktif program studi Pendidikan Akuntansi angkatan 2021-2024. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah proportionate stratified random sampling. Sampel yang digunakan dalam penelitian terdiri dari 176 mahasiswa. Teknik pengumpulan data dengan kuesioner. Uji instrumen penelitian menggunakan uji validitas dan reliabilitas. Uji prasyarat analisis menggunakan uji asumsi klasik, sedangkan uji hipotesis menggunakan uji analisis regresi berganda, uji-t, uji-F, dan koefisien determinasi berbantu program SPSS versi 26. Berdasarkan hasil penelitian dapat disimpulkan : 1) Terdapat pengaruh signifikan antara efikasi diri terhadap minat menjadi guru dengan nilai signifikansi pada uji t sebesar 0,000 (Sig. < 0,05); 2) Terdapat pengaruh signifikan antara persepsi kesejahteraan guru terhadap minat menjadi guru dengan nilai signifikansi pada uji t sebesar 0,002 (Sig. < 0,05); 3) Terdapat pengaruh signifikan antara efikasi diri dan persepsi kesejahteraan guru terhadap minat menjadi guru dengan nilai signifikansi pada uji F sebesar 0,000 (Sig. < 0,05).Kata kunci: efikasi diri, minat menjadi guru, persepsi kesejahteraan guru